Peranan Filsafat Ilmu Terhadap Undang-Undang Keperawatan - Agus Lodkha dan FL. Sudiran (Prodi Ilmu Administrasi Negara, 2016)
Philosophy science has the important role in the para medical service. There are two points of view the first is the para medical service itself and the second the education of it. The role of the philosophy in the education for the lecturers namely how to treat, teach, material and how to deliver the knowledge. In order to apply the knowledge whereas in the philosophy contents the main understanding of the human biology in the health condition and sick especially we focus the responds towards the situation. The usage of the para medical service is to find the truth about the things which are fixed that it is right or wrong. The suggestion is that the education of the para medical service is not enlarged yet in the education of it.